2010
DOI: 10.1111/j.1365-246x.1971.tb03386.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Infrasound as an Atmospheric Probe

Abstract: For four years continuous recording of infrasonic signals in the frequency range 0.1 to 1 Hz, known as microbaroms, has been conducted at Palisades, New York. The microbaroms we recorded are radiated into the atmosphere by interfering ocean waves in the North Atlantic as far as 2000 km away. A characteristic diurnal variation in the amplitude of the received signal has been noted, independent of any variation in the source. We conclude that the variation is due to variations of the factors affecting atmospheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 19 publications
1
37
0
1
Order By: Relevance
“…Assink et al, 2012) and stratosphere (e.g. Donn and Rind, 1971) cause minor, but observable variations in infrasound propagation and signal characteristics.…”
Section: Atmospheric Structure and Variabilitymentioning
confidence: 99%
“…Assink et al, 2012) and stratosphere (e.g. Donn and Rind, 1971) cause minor, but observable variations in infrasound propagation and signal characteristics.…”
Section: Atmospheric Structure and Variabilitymentioning
confidence: 99%
“…These propagation models in turn have to be used to infer the strength of any detected infrasound source for any CTBT-related infrasound monitoring activity. For this reason it is highly desirable during the establishment of such infrasound propagation models to use calibration sources which are greatly repeatable during any atmospheric conditions (DONN and RIND, 1971;GAR-CES et al, 1998;DROB et al, 2003;LE PICHON and DROB, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…During a SSW, changes in the stratospheric wind and temperature substantially influence the infrasound atmospheric waveguide, which is detectable in the infrasound observations at the ground (e.g., Donn and Rind 1971;Evers and Siegmund 2009;Hedlin and Drob 2014;Assink et al 2014a). Variations range from minor, for example, small bearing variations, to dramatic, i.e., no longer detecting a signal in a specific direction.…”
Section: Evaluation Of Forecasting Using Infrasound Remote Sensing Dumentioning
confidence: 99%
“…They are strongly affected by the stratospheric winds variability and fluctuations from GWs in the wind profiles (Le Pichon et al 2008;Kulichkov et al 2010). It was suggested in the pioneering work of Donn and Rind (1971), Rind et al (1973) and Rind and Donn (1975) that infrasound from well-identified repetitive sources could be used for remote determination of the upper-atmosphere wind speeds. IMS stations, quasi-continuously detecting infrasound from volcanoes, are well-adapted to these studies.…”
Section: Introductionmentioning
confidence: 99%